Pemberdayaan E-Warong Kube Pada Masa Pandemi Covid-19 Studi Kasus: Kota Sibolga - Muhammad Heru Akhmadi; Erin Widya Butar Butar; Erlita Nurma Wati (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2023)
Basic food programs is one type of social assistance program that helps underprivileged communities in fulfill basic food needs, providing balanced nutrition, and as an effort to prevent stunting. The distribution mechanism of this program involves the Elektronik Warung Gotong Royong Kelompok Usaha Bersama (e-Warong KUBE) as a palce of Keluarga Penerima Manfaat (KPM) to shop for food. There are 19 e-Warongs in Sibolga City, five of which are e-Warongs KUBE. This study aims to understand the empowerment of e-Warong KUBE in the basic food social assistance program in Sibolga City in 2020. This study uses a qualitative method with data collection through library research, interviews, and observations. Data processing using the Atlas.ti application. The results show that the empowerment of e-Warong KUBE has an impact on increasing and ensuring income generation, increasing business activities from the use of EDC machines, increasing the entrepreneurial spirit of e-Warong KUBE managers. There are obstacles faced by e-Warong KUBE, including the low level of participation of KUBE members, low business management skills, and high competition between e-Warongs. On the other hand, there are obstacles in the program regulator at the Sibolga City Social Service, including lack of coordination with channeling banks and difficulties in dealing with KPM's desire for conformity of basic materials with general guidelines for social assistance programs.